Diagnostic analysis of lupus anticoagulant using clot waveform analysis in activated partial thromboplastin time prolonged cases: A retrospective analysis. Issue 2 (12th March 2021) - Kanouchi, Kazunori; Narimatsu, Hiroto; Shirata, Toru; Morikane, Keita
Abstract: Background and Aims: Hemophilia was diagnosed in precedence research of clot waveform analysis (CWA) using the activated partial thromboplastin time (APTT). In patients with antiphospholipid syndrome (APS), lupus anticoagulant (LA) causes an increase in APTT, suggesting that the waveform would probably be distorted. Therefore, we evaluated using clinical samples. CWA may be useful low cost for clinical detection of LA. We assessed the clinical value of CWA for detection of LA and coagulation using clinical blood samples collected from patients with a prolonged APTT. Methods: We used patient samples inspected between April 2011 and March 2013 in Yamagata University Hospital. CWA was performed using the ACL TOP coagulation analyzer, and the associated software program was used to calculate APTT clotting endpoints. An atypical peak was defined as a derivative plot that did not conform to the normal S‐shaped clot reaction curve. Results: In total, 162 patients, including 66 men and 96 women, with an average age of 46 years (range: 24‐89 years) were included. We also collected control samples from unmatched healthy donors. All 162 patients were divided according to medication history or condition into the following five groups: heparin (n = 20), warfarin (n = 23), hepatic dysfunction (n = 13), normal (n = 20), and LA‐positive antiphospholipid syndrome (APS; n = 86). Twenty healthy individuals were included as controls. Eighty patients had an atypical peak. Among all, 78 patients (90.6%) were LA‐positive, and 2 patients (2.5%) were treated with warfarin. The remaining two patients had prothrombin time international normalized ratios (PT‐INR) >4.0 while taking warfarin. Those who were APS LA positive with thrombosis and without thrombosis had split the reaction of clotting time, deceleration/acceleration time (D/A) ratio of 2.36 (1.99, 3.24) vs 2.34 (2.04, 2.86), respectively. Conclusion: The significant atypical peak and D/A ratio extension may be explained by the clotting waveforms observed specifically in patients with LA‐positive APS.